The Fixed wing UAV usage on land use mapping for gazetted royal land in Malaysia - Hj. Mohd. Noor, Norzailawati; Harun, Nor Zalina; Abdullah, Alias (IOP Publishing Ltd, 2020)
The study deals with the usage of fixed wing unmanned aerial vehicle (UAV) in verifying boundary for gazetted royal land, which the other sight of efficacy of UAV has been tested in area of urban planning. The specific flight planning had been arranged and tested to royal land of Pekan in order to identify the settlement (kampongs) boundaries. Royal land in Pekan was the significant land that existed since 1919, which established under the Royal land Enactment 1919. It accommodated more five thousand residents in the 919 hectares of area with five villages (kampongs). The combination method of aerial mapping and vector digitization in structured a spatial database have been conducted by combining both output from UAV and GIS. The finding shows the royal land boundary was clearly identified in UAV orthophoto; further refine output of its database in GIS data. The additional info building footprints in 5 kampongs land lots also appeared very well in final output. Result shows that, the simple conclusion on the efficacy of fixed wing UAV in managing a land in urban planning, it also proved the dependency of decision makers should oriented more on geospatial applications since it was reliable and able to be used in many planning aspects in order to ensure a sustainability and resiliency of living.